Privacy and identity management : fairness, accountability, and transparency in the age of big data : 13th IFIP WG 9.2, 9.6/11.7, 11.6/SIG 9.2.2 International Summer School, Vienna, Austria, August 20-24, 2018, Revised selected papers /: fairness, accountability, and transparency in the age of big data : 13th IFIP WG 9.2, 9.6/11.7, 11.6/SIG 9.2.2 International Summer School, Vienna, Austria, August 20-24, 2018, Revised selected papers. (2019) - Unknown
No abstract available